Peran Budaya Organisasi Dalam Memoderasi Pengaruh Lingkungan Kerja Terhadap Etos Kerja Karyawan Pada SMP Muhammadiyah 1 Mlati The Role Of Organizational Culture In Moderating The Influence Of The Work Environment On Employee Work Ethics In SMP Muhammadiya - Anik Widiyanti; Muhammad Fatkhurohman Albashori (EBBANK, 2023)
Organizational culture is one of the factors that can have an impact on encouraging or even hindering the operation of an organization. The purpose of this study was to determine the effect of a moderated work environment on organizational culture on employee work ethic. The number of samples determined by all employees of SMP Muhammadiyah 1 Mlati, both educators and education staff. The research method uses validity test analysis, reliability test, classic assumption test, hypothesis test and data analysis techniques using Moderated Regression Analysis (MRA). The results showed that the work environment variable (X), organizational culture variable (Y) and the interaction variable between work environment variables and organizational culture variables (XZ) simultaneously had a significant effect on employee work ethic variables.